Serum hyperglycosylated human chorionic gonadotrophin at 14–17 weeks of gestation does not predict preeclampsia. (17th February 2014) - Keikkala, Elina; Ranta, Jenni K.; Vuorela, Piia; Leinonen, Reetta; Laivuori, Hannele; Väisänen, Sari; Marttala, Jaana; Romppanen, Jarkko; Pulkki, Kari; Stenman, Ulf‐Håkan; Heinonen, Seppo; Ghidini, Alessandro; et al.
ABSTRACT Introduction Low first‐trimester serum concentrations of hyperglycosylated human chorionic gonadotrophin (hCG‐h) predict later preeclampsia. We studied whether serum hCG‐h at 14–17 weeks of pregnancy also predicts preeclampsia alone or combined with placental growth factor (PlGF) and soluble vascular endothelial growth factor 1 (sVEGFR‐1). Methods We conducted a nested case–control study comprising 55 women with subsequent preeclampsia, 21 with gestational hypertension, 30 with a small‐for‐gestational‐age infant, and 83 controls. Serum concentrations of hCG‐h, proportion of hCG‐h to hCG (%hCG‐h), PlGF, and sVEGFR‐1 were converted to multiples of the medians (MoMs) adjusted for gestational age. Results Concentrations of hCG‐h or %hCG‐h did not differ between women with subsequent preeclampsia and controls. In women with subsequent preeclampsia, PlGF was lower (0.62 MoM) than in controls (P < 0.001). In receiver‐operating characteristics curve analysis for the prediction of preeclampsia, the area under the curve for hCG‐h or %hCG‐h was not significantly different from 0.5, whereas that for PlGF was 0.746 (95% confidence interval, 0.656–0.836; P < 0.001). Combining hCG‐h or %hCG‐h with PlGF did not improve the prognostic value. Conclusions Serum hCG‐h did not improve prediction of preeclampsia in the second trimester. © 2014 John Wiley & Sons, Ltd.